Linking soil erosion to on-site financial cost: lessons from watersheds in the Blue Nile Basin - Erkossa, Teklu; Wudneh, A.; Desalegn, B.; Taye, G. (Copernicus GmbH, 2015)
The study was conducted in three watersheds (Dapo, Meja and Mizewa) in the Ethiopian part of the Blue Nile Basin to estimate the on-site cost of soil erosion using the productivity change approach, in which crop yield reduction due to plant nutrients lost with the sediment and runoff has been analysed. For this purpose, runoff measurement and sampling was conducted during the main rainy season of 2011 at the outlet of two to three sub-watersheds in each watershed. The sediment concentration of the runoff, and N and P contents in runoff and sediment were determined. Crop response functions were developed for the two plant nutrients based on data obtained from the nearest Agricultural Research Centres. The response functions were used to estimate crop yield reduction as a result of the lost N and P assuming there is no compensation through fertilization. The results show a significant yield reduction and resultant financial loss to the farmers. Considering only grain yield of maize (Zea mays), farmers at Dapo annually lose about USD 220 ha-1 and 150 ha-1 due to the loss of N and P, respectively. In view of the importance of the crop residues, including as feed, the loss can be even greater. The study demonstrated that in addition to the long-term deterioration of land quality, the annual financial loss suffered by farmers is substantial. Therefore, on farm soil and water conservation measures that are suitable in biophysical and socio-economic terms in the landscapes and beyond need to be encouraged.